Teaching Political History within the International Relations: The Turkish Case - İsmail Köse (İnsan & Toplum)
When compared with history the discipline of International Relations (IR) seems not to have a long lasting. However, it would not be wrong to say IR has been one of the most effective sciences with its norm in the inter-state relations. With its specificity IR has an inter-disciplinary format. Although it is a comparatively young among social sciences IR, with its curriculum in Turkey, is the roof of International Law, Political History and International Relations as main sub-branches of the IR departments. If we assume IR is a tripod or a structure consisted of three pillars, International Law and Political History are the two pillars of this science. These two sciences have older traditions than IR and they also have their own independent developments. Considering this situation in this study, the position and importance of Political History in IR tried to be unearthed and views of lecturers in the field has been analyzed. Political History teaching in IR specifically has been examined, the needed scope of Political History in IR Departments, deliverance of courses in Turkish or in a foreign language, measurement and evaluation methods, lecturers expectations, challenges and gains have been examined thoroughly. In this study firstly the correlative relations pattern between the discipline of History and IR and the position of Political History in this relation have been analyzed. Later the used method and the causes and effects of this method have been explained. The backbone of the study is the set of data that has been achieved due to an online questionnaire. These data and statistical results have been analyzed with crosscheck method and graphical diagrams have been formed to ease the understandability.